MODEL BERLIAN STRATEGI INOVATIF UNTUK MENINGKATKAN AKTIVITAS, BERPIKIR KRITIS, DAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS IV SDN TELAWANG 4 - Rahmawati; Celia Cinantya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The CAR conducted in the fourth grade of SDN Telawang 4 was motivated by low student participation, critical thinking skills, and learning outcomes in mathematics. This problem arose because the learning method tended to be monotonous, so it was not able to encourage active involvement and development of students' thinking skills. As an effort to overcome this problem, the BERLIAN model was implemented, which is a combination of the PBL, MAM, and NHT models. The main focus of this study was intended to describe the increase in student activity, critical thinking skills, and learning outcomes after the implementation of the model. The study was conducted in three meetings in the even semester of the 2024/2025 academic year, with all 20 fourth grade students of SDN Telawang 4 as research subjects. The results showed a significant increase in all observed aspects. Teacher activity was in the "Very Good" criteria, student activity increased to "Almost All Students Are Very Active", critical thinking skills were at the "Almost All Students Are Very Critical" level, and learning outcomes reflected an increase with the majority of students achieving KKTP. It can be concluded that the application of the DIAMOND model is an innovative strategy that is efficient in helping to improve learning activities, critical thinking skills, and student learning outcomes.